Perlakuan Pupuk Kandang Untuk Mengurangi Dosis Pupuk Kimia Pada Budidaya Tanaman Cabai (Capsicum annuum L.): Manure Treatment to Reduce Chemical Fertlizer Dose in Chili (Capsicum annuum L.) Culture - I Komang Damar Jaya; Bambang Budi Santoso; Jayaputra Jayaputra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The use of high doses of chemical fertilizers in the production of chili (Capsicum annuum L.) has an adverse impact on the environment, especially in dryland. This study aimed to examine the role of cow manure (PKS), goat manure (PKK), chicken manure (PKA), or a combination of two manures in reducing 25% of the requirement for chemical fertilizer on chili plants. One experiment was carried out in the dryland of Gumantar Village, North Lombok Regency, from May to October 2021. Phonska NPK (15-15-15) chemical fertilizer (PK) at a 1,200 kg/ha dose was used as a control. The treatments tested were 75% PK+PKS, 75% PK+PKK, 75% PK+PKA, 75% PK+PKS+PKK, 75% PK+PKS+PKA and 75% PK+PKK+PKA. The dose of manure used in each treatment was 20 tons/ha. All treatments were repeated three times and arranged in a randomized block design. The results showed that the treatment of manure, especially goat manure and chicken manure, increased the available phosphate (P) in the soil. The growth and yield of chili plants were not significantly different in all treatments, which means that manure could replace the role of 25% of the chemical fertilizer used. These results indicate that manure in the long term can reduce the need for chemical fertilizers to produce chili in dryland. Key words: chili; dryland; manure; chemical fertilizer; nutrition